Moving towards healthy rangelands with the power of CRHWs (community rangeland health workers) - International Livestock Research Institute (CGIAR System Organization, 2025)
The HEAL (One Health for Human, Environment, Animal, and Livelihoods) project has established community rangeland health workers to provide rangeland health services. This blog provides a story of innovative steps forward by a community member to combine rangelands and human health through honey production.